Legal Regulations Regarding Cybersecurity and Corporate Legal Liability in Cases of Corporate Data Leakage in Indonesia - Elvrida Mutiara Singgih; Diana Setiawati (Universitas Muhammadiyah Surakarta, 2025)
This research discusses criminal law enforcement against current information technology in overcoming cyber crime, and to find out legal liability related to cases of company data leakage in Indonesia. This research uses a normative approach. This research uses main data and additional data. The data collection technique in this research uses literature study, while the analysis technique used in this research uses qualitative analysis. The results of this study are in the form of criminal law enforcement policies against current information technology in overcoming cyber crime, in overcoming cyber crime regulated in Law No. 19 of 2016 concerning Amendments to Law No. 11 of 2008 concerning Electronic Information and Transactions Article 27 to Article 31. Then legal liability related to cases of corporate data leaks in Indonesia, regulated in the Personal Data Protection Law which regulates data protection.